Male Remating Success and the Frequency of Copulatory Plugs in the Green Lynx Spider Peucetia viridans (Araneae, Oxyopidae) - Martin G. Ramirez; Angelik C. Achekian; Catherine R. Coverley; Rachel M. Pierce; Sarah S. Eiman; Melissa M. Wetkowski (Psyche: A Journal of Entomology)
Peucetia viridans males were allowed to mate with three virgin females and most matings resulted in live spiderlings, even when males lacked palpal paracymbial processes. Among females, the presence of copulatory plugs was inconsistent, and when present, their condition was not uniform; broken-off male paracymbia were often found in epigynal orifices. There was no size effect in a male's ability to completely plug a female's genital orifices, as well as no significant change in the pattern of plug production over consecutive mating trials. Among mated, field-collected females, the presence of plugs and paracymbia was variable, with females from some sites possessing neither structure. Field-collected females with no plugs were in significantly better condition than those with two plugs and in nearly significantly better condition than those with two paracymbia. Females in the best condition may excel at resisting the emplacement of genital obstructions and/or voiding such structures, potentially enabling them to mate with multiple males. Enhanced prey access mediated by increased water availability may be why females at two sites were in relatively better condition. If plugs help prevent sperm desiccation in inseminated females, this may have contributed to the absence of plugs from females at these two moister sites.